Sequence Analysis of the L Gene of Newcastle Disease Virus Strain AF2240 - Kusumaningtyas, Eni (2003)
Newcastle disease is an avian disease which causes a devastating effect in commercial poultry production. The causative agent for this fatal disease is Newcastle disease virus (NDV) which contains six structural proteins; nucleocapsid (NP). phospho (P). matrix (M), fusion (F). haemagglutinin-neuraminidase (HN) and large (L) proteins. The L protein of NDV is important not only as a multifunctional enzyme but also as an RNA-dependent RNA polymerase. This protein may carry out all of the enzymatic steps in transcription such as initiation, elongation and cotranscriptional modification of RNAs including capping, methylation and polyadenylation. Therefore, this study was carried out to determine the L gene sequence and its predicted translated product, and to analyse the primary and secondary structures of the L protein of the local NDV strain AF2240. In order to identify the conserved functional domains and motifs within the L protein, the amino acid composition of the L protein of strain AF2240 was compared with those of other NDV strains.